A new investigation used to predict the burst pressure in straight corroded pipes under internal pressure - Aicha Metehri; Belaïd Mechab; Bel Abbes Bachir Bouiadjra (Vojnotehnički Glasnik)
Introduction/purpose: There is a growing interest in pipeline integrity and its effects on economic and safety aspects. This study examines the process of corrosion evaluation in order to identify the remaining structural integrity of thin-walled pipelines with corrosion problems. Methods: This work aims to create a corrosion evaluation model that can analyse the deterioration of steel pipes caused by internal pressure. A study utilised the finite element approach to build models for predicting the burst pressure of defect-free straight pipes. The study involved analytical and numerical analysis and used the mathematical extrapolation method. Results: This paper discusses the impact of several factors on the integrity of a pipe, including the depth of defects, the thickness of the pipe, the shape, the size, and the position of faults, as well as the interaction between internal and external defects. Additionally, the influence of external defects on the overall integrity is discussed. Conclusion: It is concluded that the pipeline corrosion failure criterion (PCORRC) model and the presented model align with the analytical solution documented in the literature. This holds immense importance in the field of structural design and safety evaluation.